Single-cell transcriptome of mouse hippocampus identifies neural precursor-like cells, and reveals IL15Rα knock out-mediated neuron remodeling - Yanting Luo; Yadan Nie; Xuemei Huang; Haixia Wang; Zuoli Sun; Jian Yang; Yi He (BMC Genomics)
Abstract Background IL15Rα is highly expressed in brain tissues, especially in hippocampus. IL15Rα knock-out induces the behavior, physiological and molecular changes in mice similar to the phenotype of psychiatric disorders. Results To study how IL15Rα knock-out affects cellular function of the hippocampus in adult mice, we produced 64,399 single-cell transcriptomes from WT and KO mice and identified precursor-like neuron (PLN), a type of neural cells exhibiting precursor-like attributes, as well as four variant glial cell types. PLN displayed top-ranked functional changes despite barely changing in cell counts, along with high abundance of ribosomal genes, heavy energy consumption, quiescent cell-cell communication, intensive distribution in developmental stages, and a widespread yet moderate distribution across adult brain regions. We proposed PLN is in an intermediate and unprepared state, reserved for regulating inhibitory neuron fitness and exerting excitatory-inhibitory balance. We developed “polarization score” to evaluate the degree of cell aggregation and found its relation to transcription redundancy. Conclusions In summary, we demonstrate the precursor-like attributes of PLN and its potential as a regulatory fulcrum for adjusting brain’s excitatory-inhibitory balance and robustness in IL15Rα-KO mice.